Exploring the Effect of Technology Supported Suggestopedia Method on Reading Skill and Self Efficacy (Scripta : English Department Journal, 2026)
This study employed a classroom action research design to investigate whether the Suggestopedia method could improve students’ reading skills in recount texts and their self-efficacy. The participants were 16 junior high school students in Indonesia. Data were collected using reading tests, questionnaires, interviews, and classroom observations. The study was conducted in two cycles, with two meetings in each cycle. Students’ reading performance was assessed at the pre-cycle stage, at the end of Cycle I, and at the end of Cycle II to monitor their progress. The results showed a substantial improvement in students’ reading skills. The mean score increased from 51 in the pre-cycle to 65 at the end of Cycle I and further improved to 81 at the end of Cycle II. Regarding self-efficacy, the questionnaire results indicated that 74% of the students demonstrated a high level of confidence in their ability to succeed and overcome challenges in completing English reading tasks. These findings suggest that the Suggestopedia method improved students’ reading skills in recount texts while also enhancing their self-efficacy. Therefore, the Suggestopedia method can be considered an effective alternative for teaching reading, particularly recount texts, in junior high school classrooms.